Developmental-Based Classification of Enkephalin and Somatostatin Containing Neurons of the Chicken Central Extended Amygdala - Pross, Alessandra; Metwalli, Alek H.; Desfilis, Ester; Medina, Loreta (Frontiers in Physiology, 2022)
The central extended amygdala, including the lateral bed nucleus of the stria terminalis and the central amygdala, plays a key role in stress response. To understand how the central extended amygdala regulates stress it is essential to dissect this structure at molecular, cellular and circuit levels. In mammals, the central amygdala contains two distinct cell populations that become active (on cells) or inactive (off cells) during the conditioned fear response. These two cell types inhibit each other and project mainly unidirectionally to output cells, thus providing a sophisticated regulation of stress. These two cell types express either protein kinase C-delta/enkephalin or somatostatin, and were suggested to originate in different embryonic domains of the subpallium that respectively express the transcription factors Pax6 or Nkx2.1 during development. The regulation of the stress response by the central extended amygdala is poorly studied in non-mammals. Using an evolutionary developmental neurobiology approach, we previously identified several subdivisions in the central extended amygdala of chicken. These contain Pax6, Islet1 and Nkx2.1 cells that originate in dorsal striatal, ventral striatal or pallidopreoptic embryonic divisions, and also contain neurons expressing enkephalin and somatostatin. To know the origin of these cells, in this study we carried out multiple fluorescent labeling to analyze coexpression of different transcription factors with enkephalin or somatostatin. We found that many enkephalin cells coexpress Pax6 and likely derive from the dorsal striatal division, resembling the off cells of the mouse central amygdala. In contrast, most somatostatin cells coexpress Nkx2.1 and derive from the pallidal division, resembling the on cells. We also found coexpression of enkephalin and somatostatin with other transcription factors. Our results show the existence of multiple cell types in the central extended amygdala of chicken, perhaps including on/off cell systems, and set the basis for studying the role of these cells in stress regulation.